Corporate reporting and company law - Villiers, Charlotte (Cambridge University Press, 2006)
The importance of disclosure as a regulatory device in company law is widely recognized. This book explores the disclosure requirements of companies in their reporting activities, and seeks to bring together the main features of the reporting system. The book considers the theoretical basis of the corporate reporting system and describes the regulatory framework for that system. It explores financial reporting and 'narrative' reporting, highlighting the fact that financial reporting requirements are more substantially developed than narrative reporting requirements - a consequence of the shareholder-centred vision that persists in company law.